Anti-bacterial and anti-biofilm activity of probiotic bacteria against oral pathogens. (August 2016) - Ben Taheur, Fadia; Kouidhi, Bochra; Fdhila, Kais; Elabed, Hamouda; Ben Slama, Rihab; Mahdouani, Kacem; Bakhrouf, Amina; Chaieb, Kamel
Abstract: In this study, three lactic acid bacteria (LAB), isolated from barley, traditional dried meat and fermented olive were characterized and tested for their anti-bacterial and anti-biofilm activities against oral bacteria. Our results revealed that the tested LAB were γ-hemolytic and were susceptible to four antibiotics. All the strains were resistant to low pH, bile salt, pepsin and pancreatin. Furthermore, FB2 displayed a high aut-oaggregative phenotype (99.54%) while FF2 exhibited the best co-aggregation rate. Concerning the microbial adhesion to solvent, FB2 was the most hydrophobic strain (data obtained with chloroform and n-hexadecane). In addition Pediococcus pentosaceus FB2 and Lactobacillus brevis FF2 displayed a significant inhibitory effect against Streptococcus salivarius B468 (MIC = 10%). Moreover the selected strains were able to inhibit biofilm formation of Bacillus cereus ATCC14579 (MBIC50  = 28.16%) and S . salivarius B468 (MBIC50  = 42.28%). The selected LAB could be considered as candidate probiotics for further application in functional food and mainly in the prevention of oral diseases. Highlights: Three lactic acid bacteria (LAB), isolated from barley, traditional dried meat and fermented olive were characterized. The selected LAB were γ-hemolytic, resist to low pH, bile salt, pepsin and pancreatin. A significant inhibitory effect of P . pentosaceus FB2 and L . brevis FF2 against S . salivarius B468 was notice. The selected strains were able to inhibit biofilm formation of B . cereus and S . salivarius B468.